Mobile health (mHealth) technologies for fall prevention among older adults in low-middle income countries: bibliometrics, network analysis and integrative review - Dino, Michael Joseph; Thiamwong, Ladda; Xie, Rui; Malacas, Ma. Kristina; Hernandez, Rommel; Balbin, Patrick Tracy; Vital, Joseph Carlo; Rivero, Jenica Ana; Xi, Vivien Wu (Frontiers in Digital Health, 2025)
IntroductionmHealth technologies offer promising solutions to reduce the incidence of falls among older adults. Unfortunately, publications on their application to Low-Middle Income Countries (LMIC) settings have not been collectively examined.MethodsA triadic research design involving bibliometrics, network analysis, and model-based integrative review was conducted to process articles (n = 22) from 629 publications extracted from major databases using keywords related to mHealth, falls prevention, and LMIC. The web-based application Covidence and stand-alone VosViewer software were used to process data following previously published review standards.ResultsPublished articles in the field feature multidisciplinary authorships from multiple scholars in the domains of health and technology. Network analysis revealed the most prominent stakeholders and keyword clusters related to mHealth technology features and applications in healthcare. The papers predominantly focused on the development of mHealth technology, usability, and affordances and less on the physiologic and sociologic attributes of technology use. mHealth technologies in low and middle-income countries are mostly smartphone-based, static, and include features for home care settings with fall detection accuracy of 86%–99.62%. Mixed reality-based mobile applications have not yet been explored.ConclusionOverall, key findings and information from the articles highlight a gradually advancing research domain. Outcomes reinforce the need to expand the focus of mHealth investigations to include emerging technologies, update current technology models, create a more human-centered technology design, test mHealth technologies in the clinical setting, and encourage continued cooperation between and among researchers from various fields and environments.